DHA induces mitochondria-mediated 3T3-L1 adipocyte apoptosis by down-regulation of Akt and ERK. (March 2016) - Wang, An-Shi; Xu, Chen-Wei; Xie, Hong-Yan; Yao, An-Jun; Shen, Ying-Zhuo; Wan, Jing-Jing; Zhang, Hui-Qing; Fu, Jian-Fei; Chen, Zhong-Ming; Zou, Zu-Quan; Li, Duo; Zhang, Xiao-Hong
Highlights: Docosahexaenoic acid (DHA) induces cell apoptosis in 3T3-L1 mature adipocytes. The mitochondrial apoptosis pathway is involved in apoptosis of adipocytes induced by DHA. DHA induces apoptosis of 3T3-L1 mature adipocytes is mediated by the CREB/Akt and ERK signalling pathways. Abstract: Docosahexaenoic acid (DHA) possesses various bioactivities. However, the effects of DHA on adipocyte homeostasis remain unclear. Here the effects of DHA (0, 50, 100, 150 µM) on the apoptosis of mature 3T3-L1 adipocytes was investigated in order to elucidate potential mechanisms. It was shown that DHA decreased adipocyte viability, induced apoptosis, and reduced the cellular lipid content. DHA treatment also caused mitochondrial membrane potential (MMP) loss and caspase-3 activation, as well as the up-regulation of pro-apoptotic protein Bad and an increase in the Bax/Bcl-2 ratio. Additionally, treatment with DHA down-regulated the levels of CREB, total Akt, p-Akt, total ERK, and p-ERK. Our data confirmed that DHA induced mitochondria-dependent apoptosis in 3T3-L1 adipocytes and that the CREB/Akt and ERK signalling pathways were involved in DHA-triggered apoptosis, which provides new information for the development of anti-obesity strategies.